Implementation of the Least Square Method in the Forecasting System Prices of Stop Materials in the Traditional Market Unit of Palembang City - Andi Wijaya; Suzi Oktavia Kunang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to build a forecasting that makes it easier to estimate food commodity prices in traditional market units in the city of Palembang. The data used in this research are basic material data and basic material price data. This study uses the least square method as a problem solving method and method Rapid Application Development (RAD) as a system development method. The results of this study are in the form of a forecasting for staple food prices in traditional market units in the city of Palembang based on the name of the commodity and the date to be predicted, and an updated to the public.system force-casting is expected to assist the Palembang City Trade Office in providing information on food prices to the public and making strategies in the event of a price increase.